Usage Simple Present Tenses in Health Services in Belu Regency - Seuk Asa, Sefrina Maria (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
New opportunities and challenges in the health sector, especially nursing, in Belu Regency are the ability to speak English. This is influenced by the geographic location of Belu Regency which shares a land border with the Democratic Republic of Timor Leste and the planned construction of an international hospital in Belu Regency. These challenges and opportunities demand the ability to speak English for nursing, including the simple present tense. The simple present tense is the most commonly used tense in the English language. In healthcare, especially nursing, this tense is used for several purposes in line with the functions of the present tense, namely: 1) To describe events that are regular, routine, or habits that continue to occur daily. 2) To state general facts or absolute truths. 3) To express commands or instructions that must be followed. 4) To state fixed schedules or predetermined plans. 5) States a condition that may occur in the present or future.